CLINICAL AND PATHOMORPHOLOGICAL MANIFESTATIONS OF COENUROSIS (COENURUS CEREBRALIS) IN THE URAL POPULATION OF THE SAIGA ANTELOPE (SAIGA TATARICA TATARICA) - A. Kozhayeva; D. Zainettinova; B. Satybayev; N. Montayeva; A. Zhumabayev; G. Nagimova; A. Sabyrova; A. Niyatova (Animal Health and Biosafety, 2026)
Coenurus cerebralis is the larval stage of the tapeworm Taenia multiceps, representing a dangerous parasite that affects the central nervous system of wild and domestic animals and causes severe neurological disorders. In this regard, the present study comprehensively characterized the clinical manifestations, macroscopic, and histological changes associated with cerebral coenurosis registered in saiga antelopes of the Ural population in Western Kazakhstan. During the study, brain samples obtained from animals that had died under natural conditions were analyzed. Pathoanatomical examination revealed hyperemia of the meninges, migratory pathways of oncospheres, coenurus cysts at different stages of development, as well as pronounced atrophy of nervous tissue. Clinically, the affected saigas exhibited circling movements, head tilting, unsteady gait, tremors, paresis, and progressive visual impairment leading to blindness. Histological studies demonstrated the two-layered structure of the coenurus cyst wall, marked inflammatory infiltration, myelin degradation, neuronal destruction, and the presence of scolices within the cyst cavity. The most severe pathological changes were recorded in the left cerebral hemisphere. The obtained results indicate that C. cerebralis causes significant damage to the health of saiga antelopes and may contribute to a decline in population numbers. Therefore, the findings highlight the importance of early diagnosis of parasitic diseases, systematic epizootiological monitoring, and strengthening effective preventive measures.